PERAN PERATURAN KEPOLISIAN NEGARA REPUBLIK INDONESIA TENTANG PELATIHAN DAN KURIKULUM SATPAM SEBAGAI HUKUM TERAPAN DALAM SISTEM MANAJEMEN PENGAMANAN - Rini, Dhian Eka Chandra (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
We always meet the Security Unit (Satpam) in almost every place wherever we go. However, it turns out that becoming a security guard is not as easy as it is common knowledge. To carry out his profession, a security guard must go through a separate training process. This is because the security guard has a limited police function. This is enshrined in Law No.2 of 2002 concerning the Indonesian National Police, Article 3 paragraph 1 letter c. Furthermore, in Article 3 paragraph 2, it is stated that those who carry out the police function carry out the police function in accordance with the statutory regulations which form their respective legal basis. Ironically, since it was promulgated in 2002, the issue regarding the legal basis for a security guard to have the authority to act has not been explicitly regulated in the Chief of Police Regulation nor the Police Regulation (Perkap / Perpol). Likewise with the security guard related to training, coaching, and other things. So far every regulation regarding security guards established by the National Police is still limited to regulations without strict legal sanctions. Ironically, the violation of the implementation of these regulations originated with the National Police as the institution for the formation, training, guidance, supervision and evaluation of security guards. Through this paper, the author tries to describe and examine the above problems when studied from law and police science. In addition, the author also tries to examine the problems that have caused the Polri regulations not being implemented optimally. The writing of this paper uses qualitative methods, deductive-inductive, descriptive-explorative, reviewed in terms of sociology of normative law, and sociology of empirical law. This method is designed by the author so that the writer can later explore freely the uniqueness of the relevant Polri regulations regarding security guards, and examine the problems that exist in implementing the aforementioned regulations.